Pengaruh Kualitas Sumber Daya Manusia terhadap Kinerja Karyawan pada PT Taekwang Subang - Tegar Lesmana; Rini Lestari (UNISBA Press, 2022)
Abstract. In every company has a goal to develop the company through the implementation of the whole and culture and to get a big profit. It must have several resources that support it, one of which is employees. Good employee performance is supported by good quality human resources as well. The purpose of this study was to determine the quality of human resources, employee performance at PT Taekwang Subang and to examine the effect of the quality of human resources on employee performance at PT Taekwang Subang. The research method used in this study is a verification method with a quantitative approach. Sources of data used in this study is primary data sources obtained from employees of PT Taekwang Subang. The sampling technique in this study was random sampling by distributing 85 questionnaires to employees of PT Taekwang Subang. The results of this study indicate that the quality of human resources is included in the